Kunci Literasi: Jangan Paksa Anak Membaca? - Febiyanti, Nabila; Asbari, Masduki; Lestari, Silvi; Santoso, Gunawan (Jurnal Pendidikan Transformatif, 2023)
The purpose of this study was to find out Nadiem Makarim's philosophical study from the Guru Dok TV Youtube channel entitled "The Key to Literacy, don't force children to read!". In this study, the researcher used a qualitative approach with the note-taking method because the source of the data that the researcher obtained was obtained through listening. The result of a brief review of the process of listening to this philosophical study is that the role of the family is very strategic in fostering children's interest in reading. In fact, this role must be strengthened from an early age, even if it is only limited to the introduction of letters and numbers.